Internationalization of Islamic higher learning institutions in the Muslim world - Shuriye, Abdi Omar (Scholarlink Resource Centre Ltd., 2011)
The key objective of this paper is to recommend ways to internationalize Islamic higher leaning institutions, as well as underline some of the impediments to internationalization. It contends that internationalization could lead Islamic institutions to itinerancy of academic staff and students; in fact, this is one of the vital grounds as it encourages and motivates exchange for staff and students. The paper also argues that the process of internationalization will invite quality of academic standards, services and research projects. This is because through internationalization, collaboration with outside world is maintained; intercultural understanding is promoted and diversify of human resources will be enhanced. The paper further attempts to develop a framework in the process of internationalization of universities in the Muslim world.